Design and development of pumps for power plant and cars - Mohd. Noor, Alias; Abu Bakar, Rosli; Rajoo, Srithar; Ali Sera, Mardani (Universiti Teknologi Malaysia, 2003)
The development of the automobile industry in Malaysia has been very encouraging in the past years. Anyhow, this industry is confined to technology follower rather than technology leader. Thus the purpose of the project is to contribute positively to the whole process of automotive development in Malaysia. The advancement of automobile has continuously demanded more engine power requirement and thus, has increased the thermal load of the cooling system. In response to this, concern has been given to the cooling system efficiency improvement. To understand the effects of cooling system on the performance of the engine, the heat characteristics of cooling system were studied with different cooling temperatures. This range of temperatures, results in variations of engine performance, particularly the engine emission level. Engine hydrocarbon emissions increased as the coolant temperature decreases and therefore the importance of coolant temperature on the engine performance could not be neglected. As for the cooling system study, new cooling pump impellers have been designed. Series of experiments were carried out to determine the performance of the impellers as part of a water pump and also its influence to the engine performance. The new impellers produced 17% increase in the water pump efficiency. Since cooling water pump is operated by the engine itself, the efficiency improvement will therefore increase the engine efficiency by 6% or approximately 0.85kW in power gain for a 1.5 litre engine. Manufacturing study was also carried out to ensure the cost of the new impellers is within the marketing value, thus to improve its demand over conventional impeller.